An Efficient Synthetic Approach to trans‐(NHC)2Pd(R)Br Type Complexes and Their Use in Suzuki–Miyaura Cross‐Coupling Reactions. Issue 14 (13th April 2017) - Kumar, Anuj; Prakasham, A. P.; Gangwar, Manoj Kumar; Vishnoi, Pratap; Butcher, Raymond J.; Ghosh, Prasenjit
Abstract : Mixed organohalidopalladium complexes of the type trans ‐(NHC)2 Pd(R)Br were conveniently obtained from trans ‐(NHC)2 PdBr2 type complexes by a ligand‐substitution reaction. In particular, the trans ‐[1‐( 1S )‐menthyl‐4‐(R 1 )‐1, 2, 4‐triazol‐5‐ylidene]2 Pd(R 2 )Br [R 1 = Et, R 2 = CH2 Ph (3a1 ); R 1 = Et, R 2 = o ‐OMeC6 H4 (3a2 ); R 1 = R 2 = CH2 Ph (3b1 ); R 1 = CH2 Ph, R 2 = o ‐OMeC6 H4 (3b2 )] complexes were obtained from the corresponding palladium(II) precursor complexes, 2a, b, by reaction with the respective Grignard reagents, in good to excellent yields (74–93 %). Three of the four mixed organohalidopalladium complexes, 3a1, a2, b1, have been structurally characterized by single‐crystal X‐ray diffraction, which revealed the trans disposition of the NHC ligands around the palladium center. The use of these mixed organohalidopalladium complexes in the Suzuki–Miyaura cross‐coupling reaction was established for all of the complexes, 3a1 –b2, which yielded the desired cross‐coupled products upon treatment with various ArB(OH)2 [Ar = 1‐naphthyl, 4‐(1, 1′‐biphenyl), 9‐phenanthrenyl, 4‐FC6 H4, and 2, 6‐Me2 C6 H3 ] compounds, in the presence of NaOH as a base, in CH3 CN, in three hours, under reflux conditions. Abstract : A convenient access method, leading to the isolation and structural characterization of 1, 2, 4‐triazole‐based mixed organohalido trans ‐(NHC)2 Pd(R)Br (R = alkyl, aryl) type complexes, was achieved, along with their use in Suzuki–Miyaura cross‐coupling reactions, as demonstrated by reactivity studies with various aryl boronic acids.